2004
DOI: 10.1021/jm0306428
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Binding of Didemnins to Human Elongation Factor eEF1A and Rationale for the Potent Antitumor Activity of These Marine Natural Products

Abstract: Didemnins and tamandarins are closely related marine natural products with potent inhibitory effects on protein synthesis and cell viability. On the basis of available biochemical and structural evidence and results from molecular dynamics simulations, a model is proposed that accounts for the strong and selective binding of these compounds to human elongation factor eEF1A in the presence of GTP. We suggest that the p-methoxyphenyl ring of these cyclic depsipeptides is inserted into the same pocket in eEF1A th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 76 publications
2
38
0
Order By: Relevance
“…Both Cyt A and Did B inhibited translocation when aa-tRNA was loaded in an eEF1A-dependent manner ( Fig. 3D; SirDeshpande and Toogood 1995), which would be consistent with this model, since eEF2 and the ternary complex share binding sites on the ribosome (Marco et al 2004). Indeed, this mode of action has been suggested for Did B previously and is the mechanism of action of the antibiotic kirromycin (Wolf et al 1977;Ahuja et al 2000;Andersen et al 2003;Schmeing et al 2009).…”
Section: Discussionsupporting
confidence: 69%
“…Both Cyt A and Did B inhibited translocation when aa-tRNA was loaded in an eEF1A-dependent manner ( Fig. 3D; SirDeshpande and Toogood 1995), which would be consistent with this model, since eEF2 and the ternary complex share binding sites on the ribosome (Marco et al 2004). Indeed, this mode of action has been suggested for Did B previously and is the mechanism of action of the antibiotic kirromycin (Wolf et al 1977;Ahuja et al 2000;Andersen et al 2003;Schmeing et al 2009).…”
Section: Discussionsupporting
confidence: 69%
“…Drugs derived from marine organisms have recently inspired a new era in human therapy, offering vast potential for the treatment of a myriad diseases for which new, alternative therapies are desperately needed. Numerous marine compounds have been evaluated for cancer treatment, including ecteinascidin-743, [1] aplidine, [2][3][4][5] , variolin B, [6,7] lamellarins, [8] dolastatin 10, [9] jasplakinolide, [10,11] and kahalalide F. [12][13][14] In many cases, these promising compounds are peptides or depsipeptides with complex structures that favor conformational diversity. Specifically, rare residues such as d-amino acids, N-or C-alkylated amino acids, a,b-didehydroamino acids, hydroxyl acids, and structurally elaborate amino acids, such as the reverse prenyl (rPr) of two residues of Ser and Thr in Trunkamide A.…”
Section: Introductionmentioning
confidence: 99%
“…The desired structural rearrangement was achieved by progressively reducing each distance in a zipper-like fashion ( Figure 5) using a harmonic potential with a force constant that was progressively increased during several consecutive sMD runs. [107] As in the tMD Figure 4. Conformational changes in HIV-1 RT subunit p66 in going from the apo form in a covalently trapped catalytic complex (PDB entry 1rtd) to a non-nucleoside-bound inhibited form (PDB entry 1fk9).…”
Section: Energetics Of Complex Formationmentioning
confidence: 98%
“…Schematic of the steered molecular dynamics protocol implemented to drive the conformation of the catalytic domain of eEF-1A (residue numbers in pink) progressively from that found in the crystallographic complex with the guanine nucleotide exchange factor eEF-1Ba (left) to that adopted when it binds GTP (right), which is equivalent to the "GTP conformation" experimentally observed for its prokaryotic counterpart, EF-1A, also known as EF-Tu (residue numbers in cyan). [107] phate hydrolases characterized by a three-layer (aba) sandwich architecture and a Rossmann fold. Examination of the normal modes for these enzymes and exploration of the resulting structures with the CAVER tool [121] revealed that some internal motions coupled closure of the P-loop in the ATP binding site to the creation of a hydrophobic channel in the helical region that connected the deoxythymidine binding site with the bulk solvent.…”
Section: Energetics Of Complex Formationmentioning
confidence: 99%